2015
DOI: 10.4038/jnsfsr.v43i1.7917
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of precipitation in Sri Lanka

Abstract: Abstract:Two different spectral analysis methods, the multitaper method (MTM) and the maximum entropy method (MEM) were applied to investigate the presence of low-frequency periodicities in precipitation records of 14 climatological stations in Sri Lanka. The spectral analysis revealed statistically significant periodicities in the range of 2 -3 year and 3 -6 year periods in all parts of Sri Lanka irrespective of the climatic variability. The 2 -3 year band corresponds to the Quasi-Biennial oscillation (QBO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…According to Jayawardene et al [51], average rainfall in Colombo, Sri Lanka, will have a significant annual increase of 3.15 mm/year, whereas two other cities Kandy and Nuwara Eliya (about 100-200 km away Colombo) will have an annual decrease of 2.88 and 4.87 mm/year, respectively. Several other researchers including Ampitiyawatta and Guo [52], Herath and Ratnayake [53], Jayawardene et al [54], Malmgren et al [55], Ranatunge et al [56], Suppiah [57], and Wickramagamage [58] have carried out extensive research work to analyse the rainfall trends in many other important areas in Sri Lanka. However, the literature does not show any rainfall trend analysis for the Uma Oya catchment, one of the most important catchments in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…According to Jayawardene et al [51], average rainfall in Colombo, Sri Lanka, will have a significant annual increase of 3.15 mm/year, whereas two other cities Kandy and Nuwara Eliya (about 100-200 km away Colombo) will have an annual decrease of 2.88 and 4.87 mm/year, respectively. Several other researchers including Ampitiyawatta and Guo [52], Herath and Ratnayake [53], Jayawardene et al [54], Malmgren et al [55], Ranatunge et al [56], Suppiah [57], and Wickramagamage [58] have carried out extensive research work to analyse the rainfall trends in many other important areas in Sri Lanka. However, the literature does not show any rainfall trend analysis for the Uma Oya catchment, one of the most important catchments in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Jayawardene et al [5] have reported that El-Niño Southern Oscillation (ENSO) has consistently lasted for 3-4 years and that Hambantota has shown a periodicity (peak events) of 3.8 years.…”
Section: Figure1 -Main Agro-climatic Zones Of Sri Lanka [25]mentioning
confidence: 99%
“…Indian Ocean sea surface temperature is the important factor influencing the circulation or rainfall over Indian Ocean rim countries. Indian Ocean Dipole (IOD) plays an important role as a modulator of rainfall in Sri Lanka [38]. Furthermore, the influence of IOD and ENSO are statistically inter-linked and the IOD influence will be highly significant even when there is no ENSO influence and when the two are in competition, the IOD influence will prevail dominantly over that of ENSO [39].…”
Section: Enso Impact On the Seasonal Rainfallmentioning
confidence: 99%